A fotografia como dispositivo na construção do conhecimento geográfico: a experiência no mocambo - Correia, Fernando Barbosa Oliveira (2017)
This dissertation aims to understand photography, its production and reading, as a methodological device of a dialogical pedagogy in geography teaching in the 9th and 1st year classes of the Quilombola State College May 27, located in the village of Mocambo, in Port of the Leaf / SE. The present research work seeks to make reading from the photographic look that students have about their community. The study is based on a descriptive approach, supported by the qualitative research method, through intervention research and participant observation, forming itself as a case study. Previous workshops were held to guide and encourage debate. In the second moment, students were encouraged to photograph the space they experience in the community. Later, with their works in hand, the authors subtitled their photographs and dialogued collectively about them, associating the visual, textual and oral narratives. Finally, we conducted an interview with the geography teacher aiming to understand how the use of photography in the classroom, as well as its role as didactic-pedagogical didactic resource. The data collected through interview, observation and textual, visual and oral narratives have their method of analysis inspired by Bardin, seeking significance of the content, making it possible to go beyond what is not latent in the message. The final considerations point to the need to rethink the use of photography in the classroom, still very restricted to its illustrative and unreflective function. In addition, we conclude that photography, through a collective dialogue, can produce discourses about geographic knowledge, pertinent to the curriculum of geography. In this sense, photography, when used in a potential way, can be seen as an ally in the teaching and learning process.